Differential T-cell responses to a chimeric Plasmodium falciparum antigen; UB05-09, correlates with acquired immunity to malaria - Dinga, J.N.; Njimoh, D.L.; Kiawa, B.; Djikeng, Appolinaire; Nyasa, R.B.; Nkuo-Akenji, T.; Pelle, Roger; Titanji, V.P.K. (Wiley, 2016)
The development of a sterilizing and cost-effective vaccine against malaria remains a major problem despite recent advances. In this study, it is demonstrated that two antigens of P. falciparum UB05, UB09 and their chimera UB05-09 can serve as protective immunity markers by eliciting higher T-cell responses in malaria semi-immune subjects (SIS) than in frequently sick subjects (FSS) and could be used to distinguish these two groups. UB05, UB09 and UB05-09 were cloned, expressed in E. coli, purified and used to stimulate PBMCs isolated from 63 subjects in a malaria endemic area, for IFN-γ production, which was measured by the ELISpot assay. The polymorphism of UB09 gene in the malaria infected population was also studied by PCR/sequencing of the gene in P. falciparum field isolates. All three antigens were preferentially recognized by PBMCs from SIS. IFN-γ production induced by these antigens correlated with the absence of fever and parasitaemia. UB09 was shown to be relatively well-conserved in nature. It is concluded that UB05, UB09 and the chimera UB05-09 posses T-cell epitopes that are associated with protection against malaria and could thus be used to distinguish SIS from FSS eventhough acute infection with malaria has been shown to reduce cytokine production in some studies. Further investigations of these antigens as potential diagnostic and/or vaccine candidates for malaria are indicated.